Salu-salo creating sustainable Filipino communities through mixed community living - Gomez, Maria Sofia R. (College of Architecture, University of the Philippines Diliman, 2019)
Why does the housing backlog in the Philippines, which is in the millions today, constantly increase every year? Many people attribute it to the shortage of the housing supply, yet there are other factors that influence this. Many built housing projects are unlivable, as they are inaccessible and of poor quality. They are also unaffordable to the lower and middle class. Finally, many of these are socially unsustainable, such that people do not stay in these communities as there are no geniune social connections. All these problems arise from a lack of consideration of the needs of the users. Housing must be adaptable, accessible, affordable, and provide a sense of community. These are exhibited in co-living, which is a new way of living that revolves around communal spaces and flexibility. This concept can be utilized in Philippine housing to alleviate issues that are brought about by deficiencies in the accessibility and quality of housing. Communal spaces play vital roles in establishing the concepts of housing equity, social sustainability, and Philippine neighborhood. This creates a human-centric Filipino co-living model, and in turn, a sustainable and inclusive Filipino community. These are further translated through applying co-living design strategies, such as flexible design, sustainable technology, and inclusive design. Each have key features that are exemplified in the spaces, such as modular pre-fabricated systems, renewable energy, and a mixed-income community.